Development of an Educational and Innovative KIT to Support a Practicum on Reaction Rates - Nadia Nadia; Fitriani Fitriani; Rizmahardian Ashari Kurniawan (Jurnal Penelitian Pendidikan IPA, 2025)
This research is a development study that aims to design and assess the feasibility of an integrated laboratory kit for reaction materials. The development of the kit follows the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research was conducted at SMA Negeri 3 Kota Kubu Raya using purposive sampling. The research subjects consisted of 12 students from class XI MIPA 2 for a small-scale trial and 25 students from class XI MIPA 1 for a large-scale trial. Data were collected through written tests and student response questionnaires. The analysis included instrument validity testing, learning outcome analysis, and assessment of student responses to the KIT. The validation results showed that the developed KIT was suitable for use as a learning medium in terms of media and content. Student responses were also very positive, with an average questionnaire score of 80% for the learning aspect, 80% for the media aspect, and 73% for the visual communication aspect. Overall, the developed reaction KIT was considered practical, interesting, and effective for use in chemistry laboratory activities at school